The relationship of age with regional aortic stiffness and diameter - Hickson, Stacey S; Butlin, Mark; Graves, Martin; Taviani, Valentina; Avolio, Alberto P; McEniery, Carmel M; Wilkinson, Ian B (JACC. Cardiovascular imaging, 2010)
The purpose of this study was to determine the impact of age on regional aortic pulse wave velocity (aPWV). aPWV is an independent predictor of cardiovascular risk and increases exponentially with age. However, it is unclear whether such changes occur uniformly along the length of the aorta or vary by region. A total of 162 subjects, aged 18 to 77 years and free of cardiovascular disease and medication, were recruited from the Anglo-Cardiff Collaborative Trial. Cine phase contrast magnetic resonance imaging was performed at 5 aortic levels. Systolic diameter and average blood flow were measured at each level and regional aPWV (regional aPWV measured by cine phase contrast magnetic resonance imaging) determined in 4 aortic segments: the arch (R1), the thoracic-descending aorta (R2), mid-descending aorta (R3), and the abdominal aorta (R4) and across the entire aorta. Regional PWV measured by cine phase contrast magnetic resonance imaging values increased from the valve to the bifurcation in the 4 segments (PWV-R1- PWV-R4: 4.6 ± 1.5 m/s, 5.5 ± 2.0 m/s, 5.7 ± 2.3 m/s, 6.1 ± 2.9 m/s, respectively) and did not differ between genders. The greatest age-related difference in stiffness occurred in the abdominal aorta (+0.9 m/s per decade, p < 0.001) followed by the thoracic-descending region (+0.7 m/s, p < 0.001), the mid-descending region (+0.6 m/s, p < 0.001) and aortic arch (+0.4 m/s, p < 0.001). The average systolic diameters decreased moving distally (L1-5: 3.1 ± 0.4 cm, 2.3 ± 0.3 cm, 2.1 ± 0.3 cm, 1.9 ± 0.2 cm, and 1.7 ± 0.2 cm, respectively). The greatest variation in systolic diameter as a function of age occurred in the ascending region (+0.96 mm/decade, p < 0.001). Values of aPWV measured across the entire aorta were strongly correlated with PWV-tonometry (R = 0.71, p < 0.001), although they were significantly lower (mean difference 1.7 ± 1.6 m/s, p < 0.001). The greatest difference in aortic stiffness occurs in the abdominal region, whereas the greatest difference in diameter occurs in the ascending aorta, which may help offset an increase in wall stiffness.